Inovasi program motekar melalui pembelajaran jarak jauh di masa Pandemi Covid-19 SD Maruyung II - Sopia, Evip (ARKA INSTITUTE, 2022)
The purpose of this study was to evaluate the implementation of online learning and improve the quality of education at SDN Maruyung II Strategi Citra in the 2019-2020 academic year until now. This study uses qualitative data. Data were obtained from documentation and practices of education service providers at SDN Maruyung II, with samples in this study including students in grades I to VI totaling 343 students. Based on the results of the analysis, the increase in the school's image is evidenced by the increase in public trust, so that many parents send their sons and daughters to school so that the number of students increases from year to year. Facilities and infrastructure have increased from non-existent to existing; what previously existed has become better. With the Motekar Strategy, the principal became the winner of the Outstanding Principal in Tanjungsari District in 2022. So it can be concluded that the Motekar method can increase the number of teachers according to needs and qualifications.